Gambaran Perilaku Asertif Mahasiswa Semester Pertama Perguruan Tinggi X - Yeni Anna Appulembang (Provitae: Jurnal Psikologi Pendidikan, 2019)
Assertiveness manifests itself as spontaneous behaviour with a freely expressestheir feelings, aspirations, thoughts and express of speech. This study aims to findout the description of the students assertive behavior. The population in this studywere all students first grade at University X in Palembang, with samples of 67students which is male was 10 students (14.9%) and female 57 students (85.1%). Inthis research used purposive sampling techniques and the methods for collectingdata in this study used questionnaire. The instrument was constructed by Sutantri(2014) used Theory Alberty and Emmons. The format items using likert scale withscore 1 disagree strongly; 2 disagree; 3 agree and 4 agree strongly. Reliabilitycalculation used internal consistency, Alpha Cronbach With ? 0.797. Thetechniques for analyzing the data were percentage descriptive analysis andIndependent Sample t test. The result of the analysis shows that mean empiric was2,97 and mean hipotetic was 2.50 (2.97>2.50). The result of the data shows that 63(94%) students of high level category assertive behavior and 4 students (6%) of lowlevel category assertive behavior. It means that the assertive behavior of studentsin first grade at university X of high level category. In this research also assessedthe difference between assertive behavior and gender used Mann Whitney U test.The result shows that Mean Rank 66.30 (Male) and 62.17 (Female) with p valueswas 0.726 > 0.05. It means that there is no difference between assertive behaviorand gender.